2015
DOI: 10.1177/0894845315578903
|View full text |Cite
|
Sign up to set email alerts
|

Examining Longitudinal Relationships Between Dysfunctional Career Thoughts and Career Decision-Making Self-Efficacy in School-to-Work Transition

Abstract: This study examines the role of dysfunctional career thoughts between two-wave longitudinal data (Time 1 and Time 2) in career decision-making self-efficacy during school-to-work transition periods. Career decision-making self-efficacy was measured before (Time 1) and after college graduation (Time 2). The results indicated that the growth of dysfunctional career thoughts during school-to-work transition periods negatively mediated the two time points (Time 1 and Time 2) of career decision-making self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
1
22
0
5
Order By: Relevance
“…Researchers have examined the effects of planned happenstance skills on an individual's career development (Ahn et al, ; Kim, Lee, Ha, Lee, & Lee, ). Ahn et al () found that the five components of planned happenstance skills were significantly related to higher occupational identity statuses, such as achievement and moratorium, among a sample of Korean high school students.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have examined the effects of planned happenstance skills on an individual's career development (Ahn et al, ; Kim, Lee, Ha, Lee, & Lee, ). Ahn et al () found that the five components of planned happenstance skills were significantly related to higher occupational identity statuses, such as achievement and moratorium, among a sample of Korean high school students.…”
mentioning
confidence: 99%
“…Ahn et al () found that the five components of planned happenstance skills were significantly related to higher occupational identity statuses, such as achievement and moratorium, among a sample of Korean high school students. Kim et al () found planned happenstance skills contributed to increased career decision‐making self‐efficacy and decreased dysfunctional career thoughts. These results indicate that planned happenstance skills are critically important for university students to appropriately develop career paths and, taken together, demonstrate it is necessary for individuals to examine their planned happenstance skills to gain a better understanding of their career paths.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Outra hipótese versa sobre traços de resiliência, otimismo e curiosidade, os quais podem fazer as pessoas enxergarem as transições involuntárias como uma oportunidade que esperavam para mudar, convergindo com a teoria Planned Happenstance (Krumboltz et al, 2013) e com as sugestões de enfrentamento de Chen (2005). Foi comprovado que a diminuição de pensamentos disfuncionais melhora o desenvolvimento das habilidades de aprendizagem ao acaso e níveis de autoeficácia (Kim et al, 2015). E a terceira hipótese pode abarcar um indivíduo que não se satisfaz mais com o seu trabalho e que permanece no mesmo apenas em razão da remuneração recebida, sentindo os efeitos negativos do mundo corporativo, como a pressão, a falta de liberdade e de autonomia, conforme observado em trabalhadores por L. .…”
Section: Estudos Comparativosunclassified